SVCT2 Promotes Neural Stem/Progenitor Cells Migration Through Activating CDC42 After Ischemic Stroke - Yang, Yang; Zhang, Kaiyuan; Chen, Xuezhu; Wang, Ju; Lei, Xuejiao; Zhong, Jun; Xian, Jishu; Quan, Yulian; Lu, Yongling; Huang, Qianying; Chen, Jingyu; Ge, Hongfei; et al. (Frontiers in Cellular Neuroscience, 2019)
Ischemic stroke is one of the most leading diseases causing death/long-term disability worldwide. Activating endogenous neural stem/progenitors cells (NSPCs), lining in the subventricular zone (SVZ) and dentate gyrus (DG), facilitates injured brain tissue recovery in both short and long-term experimental settings. While, only a few proliferated NSPCs migrate towards the lesions to enhance endogenous repair after ischemia. Here, the results indicated that the functional recovery was evidently improved and the infarct volume was significantly reduced with ascorbic acid (AA) treatment in a dose-dependent manner from 125 mg/Kg to 500 mg/Kg, and the suitable therapeutic concentration was 250 mg/Kg. The possible mechanism might be due to activating sodium-vitamin C cotransporter 2 (SVCT2), which was down-regulated in SVZ after ischemia. Furthermore, immunostaining images depicted the number of migrated NSPCs from SVZ were significantly increased with 250 mg/Kg AA treatment or SVCT2 overexpression under the physiological and pathological condition in vivo. Besides, the data also represented that 250 mg/Kg AA or SVCT2 overexpression facilitated NSPCs migration via promoting F-actin assembling in the manner of up-regulating CDC42 expression using oxygen-glucose deprivation (OGD) in vitro. Collectively, the present study indicates that SVCT2 promotes NSPCs migration through CDC42 activation to facilitate F-actin assembling, which enlarges the therapeutic scope of AA and the role of SVCT2 in NSPCs migration after brain injury.